2019
DOI: 10.1038/s41467-019-11610-1
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated mutations in DICER1 RNase IIIa and IIIb domains exert similar effects on miRNA biogenesis

Abstract: Somatic mutations in the RNase IIIb domain of DICER1 arise in cancer and disrupt the cleavage of 5' pre-miRNA arms. Here, we characterize an unstudied, recurrent, mutation (S1344L) in the DICER1 RNase IIIa domain in tumors from The Cancer Genome Atlas (TCGA) project and MSK-IMPACT profiling. RNase IIIa/b hotspots are absent from most cancers, but are notably enriched in uterine cancers. Systematic analysis of TCGA small RNA datasets show that DICER1 RNase IIIa-S1344L tumors deplete 5p-miRNAs, analogous to RNas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 73 publications
8
80
2
Order By: Relevance
“…Interestingly, one of the latter cutaneous melanomas from the MSK‐IMPACT study harbored an additional loss‐of‐function DICER1 alteration, but it is not known whether the two alterations existed in trans . These data are supported and extended by a recent publication from Dr Eric Lai's laboratory (Vedanayagam et al, ).…”
Section: Variant Impact and Clinical Relevancesupporting
confidence: 81%
“…Interestingly, one of the latter cutaneous melanomas from the MSK‐IMPACT study harbored an additional loss‐of‐function DICER1 alteration, but it is not known whether the two alterations existed in trans . These data are supported and extended by a recent publication from Dr Eric Lai's laboratory (Vedanayagam et al, ).…”
Section: Variant Impact and Clinical Relevancesupporting
confidence: 81%
“…Because DICER1 mutations are frequently found in ultramutant tumors, DICER1 mutations in endometrial adenocarcinoma were thought to be passenger mutations. However, recent genomic profiling of tumors through TCGA PanCancer and MSK-IMPACT showed enrichment of biallelic DICER1 hotspot mutations in endometrial but not other cancers (8). Importantly, this analysis removed hypermutated tumors and the POLE subclass of endometrial cancers (8).…”
Section: Discussionmentioning
confidence: 85%
“…In vitro studies showed that hotspot mutations in the RNase IIIb domain resulted in altered miRNA processing (11)(12)(13)(14)(15). Independent studies not only validated the effects of hotspot biallelic mutations in the RNase IIIb domain resulting in miRNA biogenesis defects in human endometrial cancers but also showed that hotspot mutations in the RNase IIIa domain had similar functional effects in human endometrial cancers (8). Further, downregulation of DICER1 expression was associated with features of more aggressive endometrial adenocarcinoma, including myometrial invasion, high FIGO grade tumors, and disease recurrence (16)(17)(18).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations